2010
DOI: 10.1093/annonc/mdp294
|View full text |Cite
|
Sign up to set email alerts
|

Why do residents choose the medical oncology specialty? Implications for future recruitment—results of the 2007 French Association of Residents in Oncology (AERIO) Survey

Abstract: No data are available regarding how training in medical oncology is perceived. This study provides useful data for future policies to boost the number of oncologists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 7 publications
0
27
0
4
Order By: Relevance
“…Medical oncology also offers a broad diversity of activities, including multidisciplinary collaboration and involvement in clinical and translational research. Building on an excellent education and on a position at the centre of cancer care, young medical oncologists have a wide variety of exciting professional career opportunities to choose from in public, academic, private or industry practice [11].…”
mentioning
confidence: 99%
“…Medical oncology also offers a broad diversity of activities, including multidisciplinary collaboration and involvement in clinical and translational research. Building on an excellent education and on a position at the centre of cancer care, young medical oncologists have a wide variety of exciting professional career opportunities to choose from in public, academic, private or industry practice [11].…”
mentioning
confidence: 99%
“…Previous studies indicate that the quality and quantity of the education provided in a subject is an important factor in student decisions to specialize in that field [ 8 , 9 ]. A study completed by French oncology residents found that exposure to oncology as a medical student was a factor involved in 83% of student decisions to choose oncology as a specialty [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicate that the quality and quantity of the education provided in a subject is an important factor in student decisions to specialize in that field [ 8 , 9 ]. A study completed by French oncology residents found that exposure to oncology as a medical student was a factor involved in 83% of student decisions to choose oncology as a specialty [ 8 ]. Furthermore, a survey completed by 488 participants from 14 medical schools in the United Kingdom found that students were more likely to choose urology as a specialty if they had more hours of urology teaching, if they attended urology theater sessions, and if they had confidence in performing urological procedures [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Little information is currently available concerning young medical students desire to pursue a career in oncology. In 2011, Loriot et al [ 1 ] published a study that included only a small population of young medical oncologists. The strongest factors that had influenced their decision to become a medical oncology specialist were an interest in medical oncology, exposure to this branch of medicine during graduate training as a medical student, an interest in research, and the diverse subject area.…”
Section: Introductionmentioning
confidence: 99%